Avaliação da viabilidade da carcinicultura marinha no Estado de São Paulo: uma análise a partir de indicadores de competitividade de cadeia produtiva - Cheung, Thelma Lucchese (Universidade Federal de São Carlos, 2003)
The greater number of scientific works toward investigation of potentially and efficiency of agricultural industries study cattle breeding and agricultural sectors using their agrifood chains. On the other hand, fewer papers have investigated the aquaculture sector and its chains. This work hope to contribute to the development of aquaculture sector, evaluating the viability of shrimp farming of São Paulo (Brazil). For this purpose, we used a methodological approach which realizes analyses from competitiveness indicators of productive chains. This method consists of the identification, from its chain segment and its institutional environment, of the major competitiveness and efficiency drives. These analyses have not been still applied on studies of viability. The option for this methodology is justified because many viability studies have considered benefit-cost analysis. This analysis show low efficient when it is applied though on the productive chain level. The environment evaluation enables the identification of factors which affect competitiveness performance shrimp farming of São Paulo. The results demonstrated that both methodology can be used for the viability studies and shrimp farming of São Paulo should be improved its marketing channel and its processing industry.
Keywords: Gertenciamento da produção; Análise de viabilidade; Competitividade; Cadeia produtiva; Carcinicultura marinha; Viability; Competitiveness; Aquaculture; Productive chains; Shrimp farming; ENGENHARIAS::ENGENHARIA DE PRODUCAO